Compact sub‐6 GHz 5G‐multiple‐input‐multiple‐output antenna system with enhanced isolation - Saurabh, Arun Kumar; Meshram, Manoj Kumar (International journal of RF and microwave computer-aided engineering, 2020)
A compact two‐element multiple‐input‐multiple‐output (MIMO) antenna system with improved impedance matching and isolation is presented for future sub‐6 GHz 5G applications. The two identical tapered microstrip line fed modified rhombus‐shaped radiating elements are placed in the same orientation at a compact substrate area of 0.24λ0 × 0.42λ0 (where, λ0 at 3.6 GHz) on a shared rectangular ground. A remodeled T‐shaped ground stub is placed between a pair of radiating element to achieve improved impedance bandwidth and isolation. Further, a split U‐shaped stub connected to center of each radiating element to achieve the desired resonant frequency of 3.6 GHz. The proposed antenna covers a −10 dB operating band of 3.34 to 3.87 GHz (530 MHz) with more than 20 dB isolation between a pair of elements. MIMO performances are also analyzed and experimentally validated. The measured performances of a prototype are found in good agreement with simulated performances. Further, the simulation study is carried out to see the effect of housing and extended ground plane on two‐element MIMO antenna for practical application. An idea of realization of 12‐element MIMO is also studied using the proposed two‐element MIMO antenna.